Towards Forming an Islamic Methodology of Religionswissenschaft: The Case of Al-Biruni - Kamaruzaman, Kamar Oniah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Towards Forming an Islamic Methodology of Religionswissenschaft: The Case of Al-Biruni